EGEP BINE RITUAL TEXT FLORES TRADITION INSTITUTE COMMUNITIES: ECOLINGUISTIC PERSPECTIVE - Genua, Veronika; Larasati, Maria Marietta Bali (Denpasar Institute, 2019)
The purpose of this paper is to illustrate the tradition of Egep Bine in the Lembata Flores community. The Egep Bine tradition is a healing ritual performed by a naran 'brother' to bine 'sister for the mistakes made. The Egep Bine ritual is carried out by naran unstressed pressure and coercion so that bine avoids the disasters of benete'catastrophe' as it is difficult to obtain the kenobek 'bloodline', the huhe beria 'is full of pain that is difficult to cure' and is struck by unnatural deaths. The Egep Bine rituals are guided by molan 'shamans' as mediators between humans and ancestors. The method used is consider and competent to give an overview of the traditions of the people of Lembata. The theory used is ecolinguistics which describes the use of language related to the natural environment. The Egep Bine tradition has a morphological form that shows a lexicon related to the natural environment and related to local wisdom such as the use of braha. In an ecolinguistic perspective, everything that is used comes from the natural environment which is used as material for recovery. Examples of braha 'cotton' symbol of purity. The values contained in the Egep Bine ritual are: the value of harmony, obedience, and kinship.